Peranan Sistem Agribisnis terhadap Keberhasilan Tumpangsari Cabai-Tembakau (Kasus Subak Di Desa Sukawati, Kecamatan Sukawati, Kabupaten Gianyar) - Surata Adnyana; I Made Narke Tenaya; Dwi Putra Darmawan (Universitas Udayana, 2017)
ABSTRACTThe Role of System Agribusiness On Intercropping Success Of Chili-Tobacco(Subak Case in Sukawati Village, Sukawati Sub-District,Gianyar District)Agricultural development in Indonesia is still the mainstay and the mostimportant sectors of the overall economy. One of the way, developing the potential ofregions that still exist through horticulture and folk plantation and implement thecorrect agribusiness management system. Agribusiness as a sector of the folk economystill have bright prospects for further development, both to reinforce the folk's economyas well as Indonesia state devisa.Sukawati village very potential to develop the chili-tobacco intercroppingsystem because it has the most suitable land and widest in Gianyar district. Chilitobaccoplants have the same genus, can grow well, have local varieties that still exist,tobacco be grown are tobacco of the folk plantations who are used to the fringe.The study was conducted in the Sukawati Village that be selected purposively. Thestudy population was all the farmers who have applied intercropping farming system ofchilli-tobacco in 2013 and 2014 in 13 Subak in the Sukawati Village. The researchsample amount 90 respondents were selected by simple random sampling method. Thedata were analyzed using quantitative descriptive method and relationship analysis withthe partial least square (PLS) with help Smart PLS program.The analysis showed that are: (1) sub-systems procurement and distribution ofproduction facilities contribute positive and significant toward the intercroppingsuccess of chilli-tobacco with good category; (2) sub-systems of farming contributepositive and significant toward the intercropping success of chilli-tobacco with goodcategory; (3) sub-system of post-harvest and processing advanced contribute positiveand significant toward the intercropping success of chilli-tobacco with good category;(4) sub-system marketing contribute positive and significant to the intercroppingsuccess of chilli-tobacco with less good category; and (5) sub-system supportingservices contribute positive and significant toward the intercropping success of chillitobaccowith good category. Suggestions can be submitted are: (1) informal education of farmers in the formof field schools and training should be improved; (2) the farmer groups that have formed a cooperative to business of production facilities only fertilizers need tocooperate with village government to form village-owned enterprises (BUMDES) inorder to able to market the chilli-tobacco so that price stability can be maintained; and(3) other studies with the model and different variables need to be done further.Key words: role, agribusiness system, intercropping success